Dynamics of Macroeconomic Variables on Syariah Stock Returns in Asean Region: ARDL Analysis - Abdul Azis R.; Muhammad Yunus Kasim; I Kadek Belyoni Dwijaya; Nini Andriani; Ayu Putri Utami (Jurnal Penelitian Ekonomi dan Bisnis, 2026)
This study investigates the temporal impact of macroeconomic indicators specifically inflation, GDP growth, and foreign exchange reserves on Islamic stock returns within the ASEAN region, focusing on both short-term and long-term effects. Employing a quantitative approach with a causal design, the research utilizes the ARDL Panel model to analyze quarterly data from Sharia stock indices in Indonesia, Malaysia, Thailand, and Singapore spanning 2014 to 2023. The findings indicate that inflation negatively affects Islamic stock returns in the long term, while its short-term impact is minimal. In contrast, economic growth is found to enhance Islamic stock returns in both timeframes. Regarding foreign exchange reserves, the analysis reveals a negative long-term effect but a positive short-term effect. These conclusions highlight the importance for investors and regulators to consider macroeconomic dynamics when developing investment strategies